The Role of the English Teachers in Strengthening Character Education at the Eighth Grade of SMP Negeri 1 Lahewa Timur in 2023/2024 - Herni Trisna Lase; Yasminar Amaerita Telaumbanua; Afore Tahir Harefa; Elwin Piarawan Zebua (UIBU, 2024)
The objective of this research is to analyze English teachers' roles in strengthening character education and its obstacles. Qualitative methods with an inductive approach were used, gathering data through interviews, observations, and field notes. There are two English teachers and the eighth grade students participated in this research, which was conducted at SMP Negeri 1 Lahewa Timur. The data analysis techniques used are data condensation, data display, and verification. Results reveal three teacher roles, designing and implementing learning that integrates character values, being role models, and inspirators. Religiousness, honesty, tolerance, discipline, hard work, creativity, independence, curiosity, national spirit, love for the country, respect for accomplishment, friendliness, peace, love of reading, environmental and social care, and responsibility are all examples of integrated character values. Lesson plan analysis shows five main character value focuses: religion, honesty, responsibility, hard work, discipline, and environmental care. Obstacles include environmental factors, family, social media, and time constraints. Due to time constraints, one teacher was observed to only verbally communicate their role as an inspirator without putting it into practice in the classroom, according to the Theory of Planned Behavior.